Bibliometrix Analysis: Trade Process Information Systems in Tangerang Modern Land Market - Novita Trisetyo; Riki Riki (eCo-Buss, 2023)
Developing an information system that can facilitate the trading process at Pasar Modernland Tangerang. Pasar Modernland Tangerang is a modern market that has various types of traders and products offered to consumers. However, the trading process in this market still faces a number of obstacles, such as a lack of efficiency, lack of transparency, and difficulties in managing trade data. Therefore, this study aims to design and implement an information system that can help improve the trading process at Pasar Modernland Tangerang. Study This aim For develop system information that facilitates the trading process at Pasar Modernland Tangerang. Pasar Modernland Tangerang is a modern market that has various type merchants and products offered to consumer. The research method used in the given text is a systematic literature review. The text describes the process of conducting a bibliometric analysis to identify relevant publications for research. This study used a combination of keywords, filtering by time, type of publication, open access, language, and removal of duplicates to screen studies that fit the research objectives. This helps researchers narrow the range of studies to be synthesized and analyzed(Rojas-Sánchez et al., 2023). The information system designed and implemented in the study aimed to increase efficiency, strengthen transparency, and ease trading data management. The system covered several important features, such as trader registration and profile management, online ordering and payment, inventory management, and trading data reports and analysis. The system was expected to help increase the quality of service for consumers, make it easy for merchants to manage their business, and increase the potential growth of the economy in the market area